Brief Report: Higher ART Adherence Is Associated With Lower Systemic Inflammation in Treatment-Naive Ugandans Who Achieve Virologic Suppression. (15th April 2018) - Castillo-Mancilla, Jose R.; Morrow, Mary; Boum, Yap; Byakwaga, Helen; Haberer, Jessica E.; Martin, Jeffrey N.; Bangsberg, David; Mawhinney, Samantha; Musinguzi, Nicholas; Huang, Yong; Tracy, Russell P.; Burdo, Tricia H.; et al.
Abstract : Background: Residual systemic inflammation persists despite suppressive antiretroviral therapy (ART) and is associated with non-AIDS clinical outcomes. We aimed to evaluate the association between ART adherence and inflammation in Ugandans living with HIV who were predominantly receiving nevirapine-based ART with a thymidine analog backbone and were virologically suppressed by conventional assays. Methods: Plasma concentrations of interleukin-6 (IL-6), D-dimer, soluble (s)CD14, sCD163, and the kynurenine/tryptophan ratio, in addition to CD8 + T-cell activation, were measured at baseline and 6 months after ART initiation in treatment-naive adults who achieved an undetectable plasma HIV RNA (<400 copies/mL) at their 6-month visit. Adherence was measured through medication event monitoring system and calculated as the ratio of observed/prescribed device openings per participant. We fit adjusted linear regression models to estimate the association between ART adherence and the log-transformed plasma concentrations of inflammatory biomarkers. Results: We evaluated 282 participants (median age, 35 years; 70% women). The median (interquartile range) adherence was 93% (84–98). In the adjusted analyses, for every 10% increase in average ART adherence, we found a 15% [ P < 0.0001; 95% confidence interval (CI), −21.0 to −7.9], 11% ( P = 0.017; 95% CI, −18.3 to −2.0), and 3% ( P = 0.028; 95% CI, −5.0 to −0.3) decrease in IL-6, D-dimer, and sCD14, respectively. Conclusions: Higher ART adherence was associated with lower levels of biomarkers of inflammation, immune activation, and coagulopathy among Ugandans living with HIV who achieved viral suppression shortly after ART initiation. This suggests that ART adherence could have biological consequences beyond viral suppression. Whether ART adherence optimization in virologically suppressed individuals could reduce residual inflammation remains unknown. Abstract : Supplemental Digital Content is Available in the Text.